A comparative analysis of the role of foreign aid in post-conflict reconstruction of Rwanda and Sierra Leone - Elnour, Amna (AUC Knowledge Fountain, 2018)
Foreign aid is an essential policy instrument used to transform post-conflict countries. The purpose of this study is to measure the effectiveness of foreign aid in two post-conflict countries, Rwanda and Sierra Leone. The research seeks to deepen the knowledge of foreign aid and the structures of dependency and neoliberal policies. The study employed secondary sources of data to assess various variables such as poverty reduction, governance, education, and economic development to evaluate the effectiveness of aid. The issue of aid in post-conflict reconstruction is a complex; the management of the aid is contingent on both the donors and receipt, hence foreign aid does not automatically equate to economic growth and development. The findings of the study suggest political stability, foreign assistance, and investor-friendly policies have contributed to Rwanda’s reconstruction and economic growth. Nevertheless, Rwanda’s dependency on foreign aid remains a challenge. In contrast, Sierra Leone’s post-conflict reconstruction experience has been less successful, on one hand, foreign aid has played a positive role in the peacebuilding process, on the other hand, it has economically crippled the country and created a relationship of dependency. Foreign aid has failed to promote long-term sustainable development, and instead, has induced corruption and created a dependency syndrome. Political instability and years of prolonged war, ineffective economic policies, the mismanagement and exploitation of resources and funds, aid and the inefficiency of diversifying the economy have impaired economic growth and development. Keywords: Rwanda, Sierra Leone, foreign aid, development, exploitation